AIDS in Africa: A Security Threat? - White, Elizabeth Hadley (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Can a disease constitute a security threat? In 2000 the National Intelligence Council first identified HIV/AIDS as a threat, not only to Africa, but to the United States. This paper explores this shift from national to human security concerns and analyzes how AIDS is capable of severely impacting state structures in Africa. If AIDS is not contained in Africa in the near future, the real possibility exists of state instability and failure occurring throughout the continent. This will affect the United States on many fronts, including its national security interests.